Does Religious Affiliation Influence the Design of Corporate Governance? Evidence from the Global Microfinance Industry - Kwame Ohene Djan; Roy Mersland (Strategic Change, 2017)
Christian affiliation has a minimal impact on the design of corporate governance in microfinance organizations.
Keywords: 650